Productivity Improvement of Sandy Soil Intensively Lowland Rice by Row Inserted Planting System - SUBOWO G.; . YUSTISIA; . FIBRIANTI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
The research to increase rice planting index by row inserted planting system was conducted in sandy-loam soil of intensively lowland rice in Berbah, Yogyakarta. Yield at the initial/first rice planting was determined by N, P, and K fertilizer application, whereas inserted/second plant was determined by percentage of shadding from initial plant. The second planting (inserted at 20 days after first planting) yielded only ±50% compared to that of the first planting. Of three rice varieties studied, IR-64 had the lowest yield at the first planting, but by inserting this variety at the second planting it produced higher yield than those of Ciherang and Cimelati. The shorter plant height varieties, have a high potential to be developed into the inserted planting system. Improvement of plant distance to reduce shadding less than 50% is important to support the second plant growth. The selection of rice varieties for the first  planting and the second planting should consider the potential competition of plant from sunlight and soil nutrients. The results suggest that planting time of the second planting (insertion) should consider the availability of water and shadding potential for plant at the second planting.